Comparative transcriptome analysis reveals the regulatory effects of acetylcholine on salt tolerance of Nicotiana benthamiana. (January 2021) - Qin, Cheng; Ahanger, Mohammad Abass; Lin, Bo; Huang, Ziguang; Zhou, Jie; Ahmed, Nadeem; Ai, Suilong; Mustafa, Nabil S.A.; Ashraf, Muhammad; Zhang, Lixin
Abstract: Salinity is a major cause of crop losses worldwide. Acetylcholine (ACh) can ameliorate the adverse effects of abiotic stresses on plant growth, including salinity stress; however, the underlying molecular mechanisms of this process are unclear. Here, seedlings of Nicotiana benthamiana grown under normal conditions or exposed to 150 mmol L −1 NaCl salinity stress were then treated with a root application of 10 μM ACh. Exogenous ACh application resulted in the downregulation of the activity of the antioxidant enzymes, ascorbate peroxidase, and catalase. ACh-treated plants had lower levels of reactive oxygen species, including the superoxide anion radical and hydrogen peroxide. Transcriptome analysis indicated that ACh treatment under salt stress promoted the differential expression of 658 genes in leaves of N. benthamiana (527 were upregulated and 131 were downregulated). Gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses revealed that exogenous ACh application was associated with a substantial increase in the transcripts of genes related to cell wall peroxidases, xyloglucan endotransglucosylases or hydrolases, and expansins, indicating that ACh activates cell wall biosynthesis in salt-stressed plants. ACh also enhanced the expression of genes associated with the auxin, gibberellin, brassinosteroid, and salicylic acid signalling pathways, indicating that ACh induces the activation of these pathways under salt stress. Collectively, these findings indicate that ACh-induced salt tolerance in N. benthamiana seedlings is mediated by the inhibition of antioxidant enzymes, activation of cell wall biosynthesis, and hormone signalling pathways. Stress-induced genes involved in osmotic regulation and oxidation resistance were induced by ACh under salt stress. The genes whose transcript levels were elevated by ACh treatment in salt-stressed N. benthamiana could be used as molecular markers of the physiological status of plants under salt stress. Graphical abstract: Image 1 Highlights: Mechanisms underlying salinity stress amelioration by acetylcholine were assessed. Exogenous ACh application suppression the accumulation of reactive oxygen species. ACh treatment activated stress-related gene expression and cell wall biosynthesis in salt-stressed plants. ACh treatment induced the activation of transcription factors and hormone signalling pathways in salt-stressed plants.